2018
DOI: 10.1055/s-0038-1660871
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Radiotherapy: Changing the Treatment Sequence to Allow Immediate Free Autologous Breast Reconstruction

Abstract: From our experience, this treatment sequence allows patients to have an immediate gold standard reconstruction without an increase in surgical morbidity. It affords the benefits of IBR without concern in delaying adjuvant therapy and appears to be safe from an oncological perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…A significantly lower number of patients in the IBR group received neoadjuvant radiation therapy, as compared to the DBR group. Currently, the role of neoadjuvant radiation therapy and IBR is discussed as a feasible alternative as opposed to more traditional treatment concepts with a multimodal approach of chemotherapy, surgery, and postmastectomy radiotherapy [50,51]. Ideal timing of breast reconstruction after radiation therapy is, however, controversially debated and further studies are needed in this regard [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…A significantly lower number of patients in the IBR group received neoadjuvant radiation therapy, as compared to the DBR group. Currently, the role of neoadjuvant radiation therapy and IBR is discussed as a feasible alternative as opposed to more traditional treatment concepts with a multimodal approach of chemotherapy, surgery, and postmastectomy radiotherapy [50,51]. Ideal timing of breast reconstruction after radiation therapy is, however, controversially debated and further studies are needed in this regard [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al underscored the propensity of NART to induce deleterious tissue damage, which could potentially jeopardize subsequent reconstructive efforts, thereby suggesting a more cautious application of this modality. 13 From a mechanistic perspective, Singh et al discerningly elucidated that NART precipitated DNA damage and incited a robust immune response within the body, thereby playing a substantial role in effectuating tumor shrinkage. 14 Meanwhile, Pazos et al pioneered an avant-garde methodology of administering NART with dual objectives of minimizing collateral tissue damage and maximizing the destruction of cancerous cells, thus marking a paradigm shift in disease management.…”
Section: Preoperative Radiotherapy and Surgical Optionsmentioning
confidence: 99%
“…Hughes et al reported that the average time between NART and surgery was 6.4 weeks. 20 The institutional experience of Teoh et al advocates surgery within a median time of 2-4 weeks following NART, which may heighten the inherent surgical challenges preceding peak inflammation in wound healing. 21 Surgeons and clinical oncologists from Imperial College and Royal Marsden's Hospital developed a protocol for mastectomy and DIEP reconstruction 2-6 weeks post-radiotherapy completion (33 cases, no significant postoperative complications).…”
Section: Risks and Complications Of Preoperative Nartmentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups have been exploring the option of pre-operative radiotherapy or commonly called “reverse-sequencing radiotherapy” where radiation is delivered prior to a reconstructive procedure [ 111 ]. This pathway is attractive as it means adjuvant therapies are not delayed and also avoids expander complications and the traditional two-stage reconstruction pathway.…”
Section: The Role Of Radiotherapymentioning
confidence: 99%